The Semantic Network of the Prepositions in the Motion Event: Case Study of the Preposition إلی - Fatemeh Habibi; ‫Fathiyeh Fattahizadeh (̒Ilm-i Zabān, 2021)
This study represents the Motion Event in the verb of going in the Holy Quran, based on the structure semantic network of the preposition الی  /ila/(towards). This study aims to examine the verb of going and the preposition of الی (towards) on semantic network based on Tolmy’s Motion theory .In collecting said corpus, 88 verbs were extracted from verses consisting of the deep structure of the verb “going”; The relevant samples were collected and analyzed. The results showed that, the preposition ofالی  has the most frequent usages. This preposition represents the end-destination concept, however, its usage is not limited in this sense. Also new concepts of direction (within, outside, high) and state (mental, physical) were encoded by this preposition. One of the results of this study, is representation semantic network of the position الی, which causes the existing knowledge of this concept in the Holy Quran to be promoted.